PENGEMBANGAN MODEL PEMBELAJARAN TEMATIK INTEGRATIF EKSTERNAL DAN INTERNAL DI MADRASAH IBTIDAIYAH - Fatchurrohman, Fatchurrohman (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
The purpose of this study was to determine the learning theme thematic integrative network of external (religion and general subject) at Islamic elementary schools, the thematic learning network in integrative and internal manner (fiqh, tarih, aqeedah,akhlaq and qur’an hadith), the effectiveness of thematic integrative learning internally and externally at Islamic elementary schools by using a scientific approach. The studyused a qualitative approach to the type of Research and Development (R D) by following the model developed by Dick and Lau Cerey. The results showed that the spread of KDin sub-subjects of Islamic Education in Islamic elementary schools cannot be fitting in any theme of learning that has been prepared by the Ministry of Education. Drafting an integrative internal theme network is difficult because each sub-subject PAI has different hierarchy scientific discussion with other sub-subject PAI. After limited trial, Kn and An (fourth classroom teacher MI Mangunsari Salatiga) stated that she is comfortable andsuitable teaching with that method